2020
DOI: 10.12930/nacada-19-08
|View full text |Cite
|
Sign up to set email alerts
|

Mindset Messaging: Fostering Student Support and Confidence through Micro-Messaging in Advisor Communication

Abstract: As academic advisors help students navigate academic challenges toward a degree, seemingly mundane interactions have the potential to shape students' beliefs about themselves and their abilities. This study examines whether subtle cues within messages from advisors may help students develop what Carol Dweck calls a growth mindset—the belief that ability is malleable through effort, strategy, and help-seeking—and lead to greater perceived support from advisors and student confidence. Drawing on focus groups and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Chang et al (2015) surveyed undergraduate and graduate students and found that students prefer email communication over other communication forms, including video. Prior literature has found associations between email and growth mindset, self-efficacy, confidence and motivation (Kyte et al, 2020). Moreover, personalized messages are found to positively affect student engagement (Liu et al, 2017), which in turn influences beliefs (Alvarez-Huerta et al, 2021).…”
Section: Hypothesis Developmentmentioning
confidence: 87%
“…Chang et al (2015) surveyed undergraduate and graduate students and found that students prefer email communication over other communication forms, including video. Prior literature has found associations between email and growth mindset, self-efficacy, confidence and motivation (Kyte et al, 2020). Moreover, personalized messages are found to positively affect student engagement (Liu et al, 2017), which in turn influences beliefs (Alvarez-Huerta et al, 2021).…”
Section: Hypothesis Developmentmentioning
confidence: 87%